Parents' physical victimization in childhood and current risk of child maltreatment: the mediator role of psychosomatic symptoms - Lamela, Diogo (2013)
Objective: To test the potential mediation effect of psychosomatic symptoms on the relationship between parents' history of childhood physical victimization and current risk for child physical maltreatment. Methods: Data from the Portuguese National Representative Study of Psychosocial Context of Child Abuse and Neglect were used. Nine-hundred and twenty-four parents completed the Childhood History Questionnaire, the Psychosomatic Scale of the Brief Symptom Inventory, and the Child Abuse Potential Inventory. Results: Mediation analysis revealed that the total effect of the childhood physical victimization on child maltreatment risk was significant. The results showed that the direct effect from the parents' history of childhood physical victimization to their current maltreatment risk was still significant once parents' psychosomatic symptoms were added to the model, indicating that the increase in psychosomatic symptomatology mediated in part the increase of parents' current child maltreatment risk. Discussion: The mediation analysis showed parents' psychosomatic symptomatology as a causal pathway through which parents' childhood history of physical victimization exerts its effect on increased of child maltreatment risk. Somatization-related alterations in stress and emotional regulation are discussed as potential theoretical explanation of our findings. A cumulative risk perspective is also discussed in order to elucidate about the mechanisms that contribute for the intergenerational continuity of child physical maltreatment.